2014
DOI: 10.1017/s0029665114001669
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the nutrition transition in West Africa: implications for non-communicable diseases

Abstract: The nutrition landscape in West Africa has been dominated by the programmes to address undernutrition. However, with increasing urbanisation, technological developments and associated change in dietary patterns and physical activity, childhood and adult overweight, and obesity are becoming more prevalent. There is an evidence of increasing intake of dietary energy, fat, sugars and protein. There is low consumption of fruit and vegetables universally in West Africa. Overall, the foods consumed are predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 78 publications
4
83
0
Order By: Relevance
“…In 2003, a similar study carried out in Ouagadougou, the capital city of Burkina Faso, reported that 40.2% of participants had hypertension [22] and 33% overweight/obesity [23]. Like in the present study, high BMI (overweight/obesity) was more frequent in women, while high blood pressure in men [22,23,24,25,26]. These results indicate that the shift toward chronic diseases is taking place in Burkina Faso, particularly in its capital city, and highlight, as hypothesized, the role of urbanization in this process [27], for instance by promoting lifestyle changes, such as nutrition transition [9,28].…”
Section: Discussionsupporting
confidence: 66%
“…In 2003, a similar study carried out in Ouagadougou, the capital city of Burkina Faso, reported that 40.2% of participants had hypertension [22] and 33% overweight/obesity [23]. Like in the present study, high BMI (overweight/obesity) was more frequent in women, while high blood pressure in men [22,23,24,25,26]. These results indicate that the shift toward chronic diseases is taking place in Burkina Faso, particularly in its capital city, and highlight, as hypothesized, the role of urbanization in this process [27], for instance by promoting lifestyle changes, such as nutrition transition [9,28].…”
Section: Discussionsupporting
confidence: 66%
“…Although most West African countries are in the early stages of this transition, Ghana and other countries like Cape Verde and Senegal are at latter stages [5]. The characteristic changes in diets from traditional foods (less saturated fats and sugars, more whole grains, fruits and vegetables) to more 'westernised diets' (high in saturated fats, protein, refined carbohydrates, simple sugars and salt) and frequent consumption of fast foods has been observed in non-western societies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Foods that contain vitamins, minerals and folate are highly essential for preventing foetal damage in pregnant women (FAO/WHO, 2004). There is nutrition transition in the west African countries such as Ghana and Senegal (Bosu, 2015). There is high consumption of sugar and fatty foods leading to increasing rates of obesity by 115% since 2004 in the west African countries with less consumption of vegetables and fruits (Bosu, 2015).…”
Section: The Role Of Vegetables In Human Nutritionmentioning
confidence: 99%
“…There is nutrition transition in the west African countries such as Ghana and Senegal (Bosu, 2015). There is high consumption of sugar and fatty foods leading to increasing rates of obesity by 115% since 2004 in the west African countries with less consumption of vegetables and fruits (Bosu, 2015). Studies have shown that there is increased rate of hypertension in Burkina Faso and Cape Verde due to lack of good nutrition consumption (Busu, 2015).…”
Section: The Role Of Vegetables In Human Nutritionmentioning
confidence: 99%